(untitled) (Mediscope, 2024)
Background: The COVID-19 pandemic has been demanding possible pharmaco-therapeutic options to reduce the mortality associated with the disease by trying out the clinical efficacy of various therapeutic agents. Objective: Our purpose of the study was to explore the current pharmaco-therapeutic approaches to COVID-19 patients in different clinical categories. Methods: This is a descriptive observational study where 300 clinically diagnosed COVID-19-positive patients were included following inclusion & exclusion criteria at the study center. Patients’ demographic profiles and treatment plans were obtained using a specially designed form. The data were collated and analyzed using a Microsoft Excel spreadsheet and results were expressed in percentages. Results: Remdesivir, moxifloxacin, dexamethasone, meropenem, enoxaparin and other supportive drugs with different percentages in mild, moderate, severe & critical cases were frequently prescribed. Besides non-invasive oxygen therapy has been given in almost all patients. Conclusion: Antiviral, LMWH, broad-spectrum antibiotics, corticosteroids and other symptomatic drugs are the major treatment options for different clinical categories of COVID-19 patients. Mediscope 2024;11(1): 13-21